Prolonged Practice of Swimming Is Negatively Related to Bone Mineral Density Gains in Adolescents - Ribeiro-dos-Santos, Marcelo R. (J Bone Metab, 2016)
BACKGROUND: The practice of swimming in "hypogravity" conditions has potential to decrease bone formation because it decreases the time engaged in weight-bearing activities usually observed in the daily activities of adolescents. Therefore, adolescents competing in national levels would be more exposed to these deleterious effects, because they are engaged in long routines of training during most part of the year. To analyze the effect of swimming on bone mineral density (BMD) gain among adolescents engaged in national level competitions during a 9-month period. METHODS: Fifty-five adolescents; the control group contained 29 adolescents and the swimming group was composed of 26 athletes. During the cohort study, BMD, body fat (BF) and fat free mass (FFM) were assessed using a dual-energy x-ray absorptiometry scanner. Body weight was measured with an electronic scale, and height was assessed using a stadiometer. RESULTS: During the follow-up, swimmers presented higher gains in FFM (Control 2.35 kg vs. Swimming 5.14 kg; large effect size [eta-squared (ES-r)=0.168]) and BMD-Spine (Swimming 0.087 g/cm(2) vs. Control 0.049 g/cm(2); large effect size [ES-r=0.167]) compared to control group. Male swimmers gained more FFM (Male 10.63% vs. Female 3.39%) and BMD-Spine (Male 8.47% vs. Female 4.32%) than females. Longer participation in swimming negatively affected gains in upper limbs among males (r=-0.438 [-0.693 to -0.085]), and in spine among females (r=-0.651 [-0.908 to -0.036]). CONCLUSIONS: Over a 9-month follow-up, BMD and FFM gains were more evident in male swimmers, while longer engagement in swimming negatively affected BMD gains, independently of sex.